2022
DOI: 10.3390/ijerph19074407
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study Investigating Canadian and Australian Adolescents’ Perceived Experiences of COVID-19: Gender Differences and Mental Health Implications

Abstract: The coronavirus (COVID-19) disease pandemic has been associated with adverse psychological outcomes. This cross-cultural study (N = 1326, 71% female) aimed to investigate Canadian and Australian adolescents’ subjective experiences of COVID-19, gender differences, and psychological implications. Mixed-methods analyses were used to examine differences in COVID-19 experiences and mental health outcomes between country and gender in a Canadian (N = 913, 78% female) and an Australian sample (N = 413, 57% female) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…In terms of biographical data, findings from the ANOVA indicate that female international students are more depressed and stressed out than male international students. This finding is consistent with previous studies using university students' samples [50][51][52] and even among adolescents [53]. For Hakami et al's [51] study, they discovered that junior females who lived alone were particularly at risk of severe to extreme psychological distress.…”
Section: Discussionsupporting
confidence: 89%
“…In terms of biographical data, findings from the ANOVA indicate that female international students are more depressed and stressed out than male international students. This finding is consistent with previous studies using university students' samples [50][51][52] and even among adolescents [53]. For Hakami et al's [51] study, they discovered that junior females who lived alone were particularly at risk of severe to extreme psychological distress.…”
Section: Discussionsupporting
confidence: 89%
“…Higher scores reflect a tendency towards greater perceived stress and anxiety. Internal consistency of this scale is reported as acceptable α = 0.78 (Marie et al, 2022). For the present study, α = 0.84.…”
Section: Perceived Stress Scale -Child (Pss-c)mentioning
confidence: 54%
“…Similar to this result, Özalkan (2020) stated that the number of current students attending the courses during the distance education period was less than half. Research has shown that some similar studies have been conducted in parallel with the result of the behavioural problems seen in students during the face-to-face education period (Duan et al, 2020;Marie et al, 2022;Uçkaç, 2020). Furthermore, some other studies have been found in the related literature, in which such similar results as students' lack of computers and tablets have been reported (Aydemir, 2021;Aydın, 2021;Balaman & Hanbay Tiryaki 2021;Çilek et al, 2021;Çok, 2021;Deli, 2021;Demir & Özdaş, 2020;Karaibiş, 2021;Kavuk & Demirtaş, 2021;Laçin, 2021;Morgan, 2020;Noyan, 2022;Özdemir, 2021;Sertkaya Dinler, 2022;Seyhan, 2021;Tanta, 2021;Toraman & Kayalar, 2020;Wössmann, 2020;Uyar, 2020;Yeşilyurt, 2021;Yılmaz et al, 2021).…”
Section: Discussionmentioning
confidence: 99%